Does one year change in quality of life predict the mortality in patients with chronic obstructive pulmonary disease?—Prospective cohort study - Havlucu, Yavuz; Yorgancıoglu, Arzu; Coskun, Aysin Sakar; Celık, Pinar (Journal of Thoracic Disease, 2019)
Background: Subjects with chronic obstructive pulmonary disease (COPD) present increased mortality and poor health-related quality of life (HRQoL) as compared with the general population. The objective of this study was to evaluate whether an improvement in QoL after 1 year of proper management is a predictor of survival in a cohort of patients followed up for 10 years. Methods: In this prospective study, 306 COPD patients were assessed for eligibility between January 2003 and September 2003. Thirty-five patients were excluded due to failure to meet inclusion criteria or declining to participate and 20 patients were also excluded subsequently because they could not complete the questionnaire. Two hundred and fifty one patients were assessed at the beginning. St. George Respiratory Questionnaire (SGRQ) and pulmonary function test (PFT) were performed at the initial visit and the end of the first year. Mortality information was obtained from hospital records and direct family interviews. Results: A comparison between respiratory diseases mortality according to baseline paramaters reveals that age and presence of cardiac comorbidity indicates a higher risk of death and associated with worse QoL. After a cox regression analysis, the relative risk of death of any cause related to baseline QoL score was 1.042 (95% CI: 1.028–1.057), and 1.030 (95% CI: 1.011–1.050) for respiratory cause mortality. However, the relative risk of death when there was a deterioration in QoL after one year of follow up was 1.175 (95% CI: 1.130–1.221) for all-cause mortality and 1.214 (95% CI: 1.151–1.280) for respiratory cause mortality. Conclusions: A QoL worsening in the initial year of follow up more strongly predicts 10-year mortality of any cause and for respiratory diseases than the baseline assessment alone predicts, among patients with COPD.